Economical and low-carbon regeneration of spent LiFePO4 materials by hydrothermal relithiation - Yang, Yingpan; Liu, Zixiao; Zhang, Jialiang; Chen, Yongqiang; Wang, Chengyan (Journal of alloys and compounds, 2023)
With the increasing use of LiFePO4 (LFP) batteries, recycling spent LFP cathode materials in a green, efficient and economical way becomes essential. This study proposes a hydrothermal method directly regenerating spent LFP using low-cost Na2SO3 as a reductant, with Li2SO4 solution as the lithium source. The effects of reductant dosage, Li concentration and hydrothermal temperature were systematically investigated during LFP regeneration. The results show that both the chemical structure and electrochemical performance of the spent LFP cathode materials can be restored in the hydrothermal and reduction systems. The regeneration was performed in 6 h at 200 °C. 9 g L−1 of Li, and a 1:2 mass ratio of reductant to spent LFP was used. The regenerated LFP shows optimal electrochemical performance of 145.1, 142.7, 139.9, 135.9, 129.3, and 115.0 mAh g−1 at 0.1, 0.2, 0.5, 1, 2, and 5 C, respectively. In addition, the capacity retention rate is> 99% after 100 cycles at 1 C. The method achieved the targeted repair by bringing the Li-ions into complete contact with spent LFP in a liquid-phase environment, leading to excellent homogeneity of the regenerated LFP. This hydrothermal regeneration technique is green and economical and has potential industrial applications. [Display omitted] •A hydrothermal method was proposed to directly regenerate spent LFP.•Low-cost and safe reductant, Na2SO3, was used.•The regenerated LFP exhibits good rate performance and cycling stability.•The regeneration mechanism was clarified by various characterization means.•The regenerated LFP particles were well dispersed.